P.Re.Val.E.: outcome research program for the evaluation of health care quality in Lazio, Italy - Fusco Danilo; Barone Anna P; Sorge Chiara; D'Ovidio Mariangela; Stafoggia Massimo; Lallo Adele; Davoli Marina; Perucci Carlo A (BMC, 2012)
Abstract Background P.Re.Val.E. is the most comprehensive comparative evaluation program of healthcare outcomes in Lazio, an Italian region, and the first Italian study to make health provider performance data available to the public. The aim of this study is to describe the P.Re.Val.E. and the impact of releasing performance data to the public. Methods P.Re.Val.E. included 54 outcome/process indicators encompassing many different clinical areas. Crude and adjusted rates were estimated for the 2006-2009 period. Multivariate regression models and direct standardization procedures were used to control for potential confounding due to individual characteristics. Variable life-adjusted display charts were developed, and 2008-2009 results were compared with those from 2006-2007. Results Results of 54 outcome indicators were published online at http://www.epidemiologia.lazio.it/prevale10/index.php. Public disclosure of the indicators' results caused mixed reactions but finally promoted discussion and refinement of some indicators. Based on the P.Re.Val.E. experience, the Italian National Agency for Regional Health Services has launched a National Outcome Program aimed at systematically comparing outcomes in hospitals and local health units in Italy. Conclusions P.Re.Val.E. highlighted aspects of patient care that merit further investigation and monitoring to improve healthcare services and equity.